Tipping practices and policies in Zimbabwe's hotel industry: impacts on restaurant waiters' service delivery and work relationships - Mkono, Muchazondida (Routledge, 2021)
This study analyzes tipping practices and policies in Zimbabwe's hotel industry from the perspective of restaurant waiters. The majority of respondents reported that discretionary tipping, as opposed to service charges, is the norm and that most hotels have a tip-pooling system. The findings show that guests who are expected to tip well, based largely on stereotypes as well as past tipping behavior, get better service treatment from waiters. Among themselves, waiters said that the culture of tipping has a huge impact on their work relationships. Most waiters presumed the pooling of tips to be an unfair practice.